2017
DOI: 10.1073/pnas.1704258114
|View full text |Cite
|
Sign up to set email alerts
|

Topological impact of noncanonical DNA structures on Klenow fragment of DNA polymerase

Abstract: Noncanonical DNA structures that stall DNA replication can cause errors in genomic DNA. Here, we investigated how the noncanonical structures formed by sequences in genes associated with a number of diseases impacted DNA polymerization by the Klenow fragment of DNA polymerase. Replication of a DNA sequence forming an i-motif from a telomere, hypoxia-induced transcription factor, and an insulin-linked polymorphic region was effectively inhibited. On the other hand, replication of a mixed-type G-quadruplex (G4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 47 publications
(66 reference statements)
3
113
0
Order By: Relevance
“…From the therapeutic view point, we investigated whether the structural transformation by Fis influenced the replication reaction. Previously, we reported that the replication reaction can be affected by the formation of non-canonical structures on the template DNA and that the i-motif especially blocked the processivity of DNA polymerase efficiently 10 . For the replication analysis, a fluorescein-labelled primer and template DNA containing VEGF IM was designed as reported previously 10 .…”
Section: Effects Of Loop Sequence Of Vegf Im On Its Structural Transfmentioning
confidence: 99%
“…From the therapeutic view point, we investigated whether the structural transformation by Fis influenced the replication reaction. Previously, we reported that the replication reaction can be affected by the formation of non-canonical structures on the template DNA and that the i-motif especially blocked the processivity of DNA polymerase efficiently 10 . For the replication analysis, a fluorescein-labelled primer and template DNA containing VEGF IM was designed as reported previously 10 .…”
Section: Effects Of Loop Sequence Of Vegf Im On Its Structural Transfmentioning
confidence: 99%
“…Only recently,t he i-motifs in promoter and telomeric regions were proposed to be implicated in the regulation of transcription [3] and the integrity of telomeric DNA. [4] However,d espite all available indications of i-motif function in vivo,t he biological relevance of i-motifs has remained am atter of dispute for the following reasons:1 )The lack of direct experimental evidence for the existence of i-motifs in vivo and 2) the very strong dependence of i-motif stability on chemical and physical environmental factors such as pH that generally appear to be incompatible with the parameters of the intracellular space.W hile i-motifs are rather stable in acidic pH, low ionic strength, and dehydrating conditions,the propensity for i-motifs is generally lower under simulated physiological conditions comprising relatively high ionic strength (ca.…”
mentioning
confidence: 99%
“…[12] In biological terms,o ur results support the concept that i-motif structures may act as active regulators of genomic DNAa nd potential drug targets. [3,4,13] …”
mentioning
confidence: 99%
“…DNA i‐motifs are four‐stranded structures consisting of two parallel DNA duplexes zipped together by the intercalation of protonated cytosine–cytosine (C.CH + ) base pairs . These i‐motifs have recently been postulated to be actively involved in the regulation of DNA transcription . However, because i‐motif formation was never directly observed in vivo and because the formation of DNA i‐motifs is promoted by low ionic strength and acidic pH , that is, factors that are rather inconsistent with the physiological cellular environment, the existence of i‐motifs in vivo has been controversial.…”
Section: In‐cell Nmr Spectroscopymentioning
confidence: 99%